Transformasi Sistem Pengendalian Manajemen di Era Digital: Kajian Kepustakaan mengenai Digitalisasi, Sistem Pengendalian Manajemen, dan Kinerja Organisasi - Riska Rahayu; Aceng Abdul Hamid (Al-Makki Publisher, 2026)
Digital transformation has fundamentally reshaped the way organizations design and operate their Management Control Systems (MCS), yet most prior studies still examine the strategic, behavioral, and digital dimensions of MCS separately, leaving their conceptual interrelation insufficiently mapped. This article aims to map the development of MCS concepts from a classical toward a digital perspective, to analyze the interrelation among the strategic, behavioral, and digital dimensions of contemporary MCS, and to formulate a theoretical proposition regarding the relationship between MCS digitalization and improved organizational performance. This study employs a qualitative approach through library research, with data collected via documentation techniques from relevant journal articles, books, and official institutional reports, and analyzed using content analysis and thematic analysis techniques through data reduction, data display, and conclusion drawing. The findings show that MCS has transformed across four main dimensions (tasks, instruments, organization, and behavior) that can be synthesized into three broader dimensions—strategic control, behavioral control, and digital control—which are interrelated and mutually reinforcing. MCS digitalization is found to be positively associated with improved organizational performance across financial, operational, managerial, and accountability dimensions, although this relationship is contingent and strongly influenced by human resource readiness, technological infrastructure, digital leadership, and organizational culture. This study contributes an integrative three-dimensional framework of digital MCS that may serve as a conceptual foundation for further empirical research as well as for management control practice in the digital era.